2010
DOI: 10.1625/jcam.7.43
|View full text |Cite
|
Sign up to set email alerts
|

A Safety Study on the Long-Term Consumption of Astaxanthin in Healthy Human Volunteers

Abstract: A long-term safety study was conducted with astaxanthin derived from Haematococcus pluvialis algae extract. Fifteen healthy volunteers took 9 mg of astaxanthin daily for 12 weeks. Physiological (including doctor's consultation), haematological, biochemical, and urinary markers were examined at weeks 0, 4, 8 and 12. No adverse effects or clinical changes were observed throughout the test period. It was concluded that a healthy adult can consume 9 mg of astaxanthin derived from Haematococcus pluvialis algae extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…We have identified and evaluated 87 clinical trials ( As shown in Table 3, eight human studies were conducted to look specifically at safety of high doses of natural AX, ranging from 8 to 45 mg/day and over 4 to 12 weeks (Aquasearch, 1999;Kajita et al, 2010;Kajita, Tsukahara, Kato, & Yoshimoto, 2009;Matsuyama et al, 2010;Ohgami et al, 2005;Satoh et al, 2009;Spiller & Dewell, 2003;Tsukahara et al, 2005). Twenty-eight studies were found, which used daily doses of at least 12-mg natural AX over a period of at least 4 weeks.…”
Section: Clinical Safety Of Natural Axmentioning
confidence: 99%
“…We have identified and evaluated 87 clinical trials ( As shown in Table 3, eight human studies were conducted to look specifically at safety of high doses of natural AX, ranging from 8 to 45 mg/day and over 4 to 12 weeks (Aquasearch, 1999;Kajita et al, 2010;Kajita, Tsukahara, Kato, & Yoshimoto, 2009;Matsuyama et al, 2010;Ohgami et al, 2005;Satoh et al, 2009;Spiller & Dewell, 2003;Tsukahara et al, 2005). Twenty-eight studies were found, which used daily doses of at least 12-mg natural AX over a period of at least 4 weeks.…”
Section: Clinical Safety Of Natural Axmentioning
confidence: 99%